Detection of cartel evidence: a case study for Belém/PA and Santarém/PA using volatility models (Research, Society and Development, 2021)
The aim of this paper is to detect evidence of cartel in the application of volatility models in price data of gas dealers in the municipalities of Belém/PA and Santarém/PA. Cartels are coordinated actions between firms in which there are tacit or explicit agreements aimed at price coordination, quantities offered and/or market slices, to maximize profit jointly. For the detection of cartels, arch, GARCH, EGARCH and TGARCH volatility models will be applied. The data used are the average weekly gasoline prices extracted from the official portal of the National Agency for Petroleum, Natural Gas and Biofuels (ANP), in the period from 2004 to 2020. The results of the equation for mean showed no indications of cartel, while the ARCH model for variance detected only in Belém. There were no indications of the presence of asymmetric shocks in the Belém series, with only the occurrence in Santarém. It is concluded that the methodology is useful for the detection of cartels of gasoline dealers.